Modern therapeutic principles in the fight against hypertension - Tomić, Maja (Archives of Pharmacy, 2022)
Hypertension is the major modifiable cardiovascular (CV) disease risk factor. Despite the availability of numerous efficacious and safe medications and non-pharmacological measures, rates of blood pressure (BP) adequate control in hypertensive patients are not satisfactory, both in Serbia and in the world. Lifestyle adjustments (dietary sodium limitation, weight reduction, healthy diet, regular physical activity, alcohol consumption moderation and smoking cessation) remain the basic component of successful hypertension treatment and lowering overall CV risk. First-line antihypertensive agents are angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, calcium channel blockers, thiazide/thiazide-like diuretics, and β-blockers (the latter are first-line agents only in presence of a compelling comorbidity). These classes of antihypertensives have an advantage over others because, in addition to lowering BP, they have been shown to reduce the risk of major CV events (myocardial infarction and/or stroke) and death in hypertensive patients. Majority of the latest guidelines give primacy to the combination of antihypertensive agents from the very beginning of treatment for most patients. By combining drugs that target different mechanisms involved in BP regulation, greater efficacy and/or improved tolerability may be achieved, due to additive or synergistic interaction between components. Utilization of single-pill containing two or more antihypertensive agents enables improving patient adherence. Second line antihypertensive agents (mineralocorticoid receptor antagonists, centrally acting agents, α-blockers, vasodilators and other classes of diuretics) are added when satisfactory BP control cannot be achieved with first-line drugs combinations or when comorbidities favor their use. Device-based treatments (e.g. renal denervation) are reserved for treatment of pharmacologically intractable hypertension.